Trans-generational immunization in the acrobat ant Crematogaster scutellaris. (30th April 2018) - Bordoni, Adele; Dapporto, Leonardo; Tatini, Irene; Celli, Martina; Bercigli, Manuel; Ressurrección Barrufet, Serena; Perito, Brunella; Turillazzi, Stefano
Abstract : Trans-generational immunization is defined as the transmission of an enhanced resistance to a pathogen from parents to offspring. By using the host–parasite system of the ant Crematogaster scutellaris and the entomopathogenic fungus Metarhizium anisopliae, we describe this phenomenon for the first time in ants. We exposed four groups of hibernating queens to different treatments (i) a non-lethal dose of live conidiospores in Triton, (ii) a dose of heat-killed conidiospores in Triton, (iii) a control Triton solution, and (iv) a naive control. We exposed their first workers to a high dose of conidiospores and measured mortality rates . Workers produced by queens exposed to live conidiospores survived longer than those belonging to the other groups, while exposure to Triton and dead spores had no effect. Starved workers showed a significantly higher mortality. The treatments did not influence queen mortality, nor the number of offspring they produced at the emergence of the first worker, showing no evidence of immunization costs—at least for these parameters in the first year of colony development. We propose that trans-generational immunization represents an important component of social immunity that could affect colony success, particularly during the critical phase of claustral foundation.